Modern terrarium studio - George, Megan frey50; Smith, Michelle (Cincinnati, Ohio Fons & Porter, 2015)
Presents 25 easy-to-make terrariums and living landscapes that push the boundaries of traditional terrarium design.
"Design + build custom landscapes with succulents, air plants + more."
Includes index
Keywords: Terrariums